CHARACTERIZATION OF THE WORK CONTEXT AND QUALITY OF LIFE OF FAMILY HEALTH STRATEGY PROFESSIONALS - Maria Beatriz Guimarães Ferreira; Márcia Marques dos Santos Felix; Divanice Contim; Delvane José de Souza; Ana Lúcia de Assis Simões (Universidade Federal do Paraná, 2015)
The present study aimed to characterize the work contextand quality of life of Family Health Strategy (FHS) professionals.Observational, cross-sectional and qualitative study with 256 Family Health Strategy professionals. The data was collected from September 2013 to January 2014 using the Scale of Assessment of the Work Context and the WHOQOL-BREF tool.Exploratory and bivariate analyses were used for the data. The factor Work Organization showed the highest score, and Socio-professional Relations, the lowest score. In the domains of quality of life, the Social domain obtained the highest score, and the Environmental domain obtained the lowest score. Also, thepoorest work context led to the lowest scores of quality of life.It is essential to understand the work context of health professionals, since it can affect their quality of life and work, with impact on the care delivered.